A COMPARATIVE STUDY OF EFFICACY ON GLYCEMIC CONTROL BY GLIMEPIRIDE VERSUS TENELIGLIPTIN AS AN ADD ON TO METFORMIN THERAPY IN TYPE 2 DIABETES MELLITUS PATIENTS - BOMMINENI, SASHIDHAR REDDY; SHRAVANI, P.; SHYAM, J.; ALEKHYA, M.; SRIKANTH, B. (International Journal of Current Pharmaceutical Research, 2022)
Objective: In our study, the objective was to evaluate the effectiveness of glycemic control of Glimepiride versus Teneligliptin for 2nd-line therapy in combination with Metformin in T2DM patients. Methods: A Randomized, Observational, Prospective study has been conducted in outpatient and inpatient departments of General Medicine in RVM Hospital (Laxmakkapally, Mulugu, Siddipet, Telangana). A total of 100 patients with T2DM were recruited in our study in which 50 patients were in Group A (Metformin-Glimepiride) and the other 50 patients were in Group B (Metformin-Teneligliptin). The comparative assessment of efficacy was conducted using glycemic parameters such as FBS, PPBG and HbA1c to interpret the results. Results: The mean difference values of HbA1c pre-treatment and post-treatment of Group A were calculated as 1.47 and of Group B was 0.83. The mean difference values FBS pre-treatment and post-treatment of Group A were found to be 56.96 and Group B was 29.62. The PLBS mean difference at Pre-treatment and Post-treatment of Group A and Group B was obtained to be 115.8 and 52.58, respectively. Conclusion: From the results obtained, we hereby conclude that, though there was no large difference between the lowering of HbA1c values by two Groups, the FBS and PLBS levels were diminished significantly by Group A (Metformin-Glimepiride) than Group B (Metformin Teneligliptin). Therefore, Glimepiride is considered to be more beneficial than Teneligliptin when combined with Metformin Monotherapy.